Chemistry for environmental scientists - Möller, Detlev (De Gruyter, 2022)
"The second edition of this book presents the fundamentals of chemistry in light of their importance for the environment and environmental processes. The new edition includes updated references and a more practical approach to the topic. The comprehensive discussion is structured in three parts: introducing the theory of physical chemistry, evaluating elements and compounds, and presenting principles of environmental chemistry."-- Publisher's description.
Previous edition: 2015.
Keywords: Environmental chemistry.; Air.; Atmosphere.; elektronické knihy; electronic books